2014
DOI: 10.3892/br.2014.357
|View full text |Cite
|
Sign up to set email alerts
|

Association between Hcy levels and the CBS844ins68 and MTHFR C677T polymorphisms with essential hypertension

Abstract: The aim of the present study was to investigate the association between the homocysteine (Hcy) levels and polymorphisms of the and genes in essential hypertension (EH). The effects of the and haploid genotypes and the combined genotypes on EH and levels of Hcy were further explored. The polymorphisms of and genes in 200 EH and 200 normal tensive (NT) patients were detected using polymerase chain reaction-restriction fragment length polymorphism and analysis of the distribution of genotypes. An automated bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…On the other hand, gender, FBS, HDL-C, and BMI were not observed to be risk factors. These results are comparable to the study of Cai et al (2014), where significant differences between the two groups were observed for LDL-C, TC and TG but not HDL-C in a Chinese Han population in Xinjiang Shihezi, China. Their results also revealed dependency of EH on FBS but not age.…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, gender, FBS, HDL-C, and BMI were not observed to be risk factors. These results are comparable to the study of Cai et al (2014), where significant differences between the two groups were observed for LDL-C, TC and TG but not HDL-C in a Chinese Han population in Xinjiang Shihezi, China. Their results also revealed dependency of EH on FBS but not age.…”
Section: Discussionsupporting
confidence: 79%
“…Methylenetetrahydrofolate reductase C677T and CBS844ins68 may exist with a certain linkage and the T-D haplotype may be a risk factor for HTN. 37 However, the exact mechanisms underlying the potential association between Hcy and HTN risk require future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations at MTHFR rs1801133 can result in 50%-60% reduced enzyme activity (van der Put et al, 1998), which can have significant developmental consequences. Previous studies have shown that Hcy levels were significantly higher in the TT genotype at MTHFR rs1801133 compared to that in the CT and CC (Cai, Yin, Yang, Zhang, & Cheng, 2014). The FR protein contains several putative surface lysine residues which may be susceptible to the posttranslational modification known as homocysteinylation (Cabrera et al, 2008).…”
Section: Discussionmentioning
confidence: 99%